Cytokinins beyond plants: synthesis by Mycobacterium tuberculosis - Marie I. Samanovic; K. Heran Darwin (Microbial Cell, 2015)
Mycobacterium tuberculosis (M. tuberculosis) resides mainly inside macrophages, which produce nitric oxide (NO) to combat microbial infections. Earlier studies revealed that proteasome-associated genes are required for M. tuberculosis to resist NO via a previously uncharacterized mechanism. Twelve years later, we elucidated the link between proteasome function and NO resistance in M. tuberculosis in Molecular Cell, 57 (2015), pp. 984–994. In a proteasome degradation-defective mutant, Rv1205, a homologue of the plant enzyme LONELY GUY (LOG) that is involved in the synthesis of phytohormones called cytokinins, accumulates and as a consequence results in the overproduction of cytokinins. Cytokinins break down into aldehydes that kill mycobacteria in the presence of NO. Importantly, this new discovery reveals for the first time that a mammalian bacterial pathogen produces cytokinins and leaves us with the question: why is M. tuberculosis, an exclusively human pathogen, producing cytokinins?